2020
DOI: 10.20944/preprints202003.0009.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing Sustainability Performance at the Farm Level: Examples from Greek Agricultural Systems

Abstract: In recent years, farmers and policymakers have faced ample challenges and have struggled to support the sustainability of the agricultural sector. Sustainable agriculture encompasses multiple concepts, and its performance produces extensive debate about data requirements, appropriate indicators, evaluation methods, and tools. Under the European Union (EU) financed project FLINT (Farm Level Indicators for New Topics in policy evaluation), detailed data have been collected at the farm level to provide broader co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Recently, another pressure on olive groves-the urban sprawl-has begun to exert its influence. The main issue here is to achieve sustainability, and it is important to develop farm-scale approaches such as that we developed in Bailén or those developed by Tzouramani et al (2020) in Greece and Palese et al (2013) in Italy.…”
Section: Farmer Income Is Climate Dependent: Implications For Sustainable Agriculturementioning
confidence: 99%
“…Recently, another pressure on olive groves-the urban sprawl-has begun to exert its influence. The main issue here is to achieve sustainability, and it is important to develop farm-scale approaches such as that we developed in Bailén or those developed by Tzouramani et al (2020) in Greece and Palese et al (2013) in Italy.…”
Section: Farmer Income Is Climate Dependent: Implications For Sustainable Agriculturementioning
confidence: 99%
“…The AHP approach was developed by Saaty (1986) and involves three basic steps to (a) structure the criteria into a hierarchic system, (b) use the surveyed data to calculate the pairwise comparison matrices and the relevant statistics (e.g., the eigenvectors, the consistency index and the consistency ratio), and (c) assess the relative important of each criteria in different hierarchies. The details of those steps can be found in Saaty (1986), Rezaei‐Moghaddam and Karami (2008) and Tzouramani et al (2020), among others.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Liang and Peng (2017) identified that manpower input is the most important factor whilst geographic location is the least important one in the autonomous landscape development of rural communities in Taiwan. In Greece, Bartzas and Komnitsas (2020) designed an environmental AHP model to identify the most sustainable agricultural management practices at regional level whilst Tzouramani, Mantziaris, and Karanikolas (2020) examined the sustainability performance at the farm level. In a similar vein, Hai, Hai, Y, and Hens (2009) used the AHP approach to analyse 16 health and environmental indicators of sustainable development in a central province in Vietnam and found that this development was weak during the 2000-2005 period.…”
mentioning
confidence: 99%
“…Step 1: For each of the farms, the environmental, economic, and social variables will be evaluated, taking into account the variables described in the methodology. (24) Step 2: For each of the categories, the variability of the variables is analyzed and those that have constant values or do not have information on at least 50% of said variable in the farms are not considered in the study (25)(26) of NA.…”
Section: Table 3 Description Of Algorithm L: K-meansmentioning
confidence: 99%